Abuse of the Rights of a Taxpayer: Comparative Law Aspect - A. A. Malinovsky (MGIMO University Press, 2013)
The term “misuse of the rights of a taxpayer” is analyzed in this article. Foreign law doctrines on misuse of the rights of a taxpayer are examined, foreign legislation and court practice.